Effects of fertilizers and vesicular-arbuscular mycorrhizas on the growth and photosynthesis of Azadirachta excelsa (Jack) Jacobs seedlings - Huat, Ong Kian; Awang, Kamis; Hashim, Azizah; Majid, Nik Muhamad (Elsevier, 2002)
Azadirachta excelsa (Jack) Jacobs is a fast growing indigenous species being promoted as a plantation species in Malaysia. However, the low fertility of most native soils is a primary constraint for good establishment of this species. The effects of fertilizer and vesicular-arbuscular mycorrhizal infection on growth and rate of photosynthesis in A. excelsa seedlings were assessed in a pot experiment. The mycorrhizal inoculated plants (without fertilizer) grew more slowly than control (uninoculated without fertilizer) seedlings, despite the higher percentage of infection. These results suggest that introduced mycorrhizal inoculum was not effective enough to improve seedling growth. Mycorrhizal development was depressed under high levels of fertilizer application. Fertilizer had the strongest effect on growth, biomass and photosynthetic rate, and leaf nutrient concentrations of A. excelsa seedlings. Plants supplied with slow release fertilizer (20N-10P2O5-5K2O) alone gave the most vigorous growth and higher rates of photosynthesis among the fertilizer treatments. These results demonstrate the potential of using slow release fertilizer in promoting seedling growth.